Effects of gamma irradiation on sugars, fatty acids and tocopherols of chestnuts (Castanea sativa Miller) - Barros, Lillian (2011)
As seasonal products chestnuts have to be postharvest treated to increase their shelf-life. The most common preservation method for chestnuts is the use of chemical fumigation with methyl bromide, a toxic agent that is under strictly use under Montreal Protocol due to its adverse effects on human health and environment. Food irradiation is a possible feasible alternative to substitute the traditional quarantine chemical fumigation treatment. The main studies in chestnuts irradiation were done in an Asian variety, which is bigger and sweeter than the European types. However, on Portuguese varieties nothing has been reported. Herein, the influence of irradiation and storage time in sugars, fatty acids and tocopherols profiles/quantities in chestnuts obtained in Trás-os-Montes, Northeast Portugal, was evaluated for the fist time.